Hospital admission rates and the prevalence of asthma symptoms in 20 local authority districts. Issue 8 (August 1991) - Burney, P G; Papacosta, A O; Withey, C H; Colley, J R; Holland, W W
Abstract : Representative samples of 20-44 year old men living in 20 local authority districts in England were surveyed in 1986 by postal questionnaire and asked about symptoms associated with asthma and treatment for asthma. Regional health authorities provided information on all hospital discharges of men of the same age living in the same districts. Specific information was also provided on discharges where the primary cause of admission was for asthma. Admission rates for asthma were related to the prevalence of night time breathlessness and independently to the all cause admission rate for men of the same age. Admission rates were not significantly related to prescription rates of either corticosteroids or beta 2 agonists for symptomatic men. This lack of association is hard to interpret without further information on variation in the severity of disease. These data show that admission rates for asthma are not dictated solely by health service characteristics, such as availability of beds or the "style" of the physician, but also reflect need. More research is required on how best to reduce the local prevalence and severity of asthma.